Childhood Dermatitis Neglecta on a Vitiligo Patch - Sonal Sachan; Vandana Yadav; Harshit Jaiswal; Divya Prajapati (Indian Journal of Paediatric Dermatology)
Dermatitis neglecta is an uncommon skin disease caused by poor hygiene. Diagnosis requires a high degree of clinical suspicion, especially when dealing with childhood cases, due to misinformation and concealment. The important risk factors in the present case included inadequate hygiene, a painful traumatic wound, and repeated insults from the application of a plant allergen without washing. This led to the formation of characteristic cornflake-like scaling of the lesions. Epidermal changes in the histopathology and good therapeutic response to cleansing with soap-water helped in making the diagnosis. This case was interesting because all this occurred on a vitiligo patch, which complicated the diagnosis.